Cochlear Implants in Single-Sided Deafness. Comparison Between Children and Adult Populations With Post-lingually Acquired Severe to Profound Hearing Loss - Falcón Benítez, Nadia; Falcón González, Juan Carlos; Ramos Macías, Ángel; Borkoski Barreiro, Silvia; Ramos de Miguel, Ángel (Frontiers in Neurology, 2021)
Objective: To determine audiological and clinical results of cochlear implantation (CI) comparing two populations with single-sided deafness (SSD): post-lingually deaf children between 6 and 12 years of age, and post-lingually deaf adults, in order to evaluate the effect of CI in different age groups. Design: Retrospective case review. Setting: Tertiary clinic. Patients and Method: Twenty-three children and twenty-one adult patients that were candidates for CI with single-side deafness were included. In all cases we evaluate: Speech perception thresholds; disyllabic words test (65 dB SPL) were performed in the modalities S0–SCI–SNH and Auditory Lateralization Test. The Speech, Spatial, and Qualities of Hearing Scale (SSQ) questionnaire was also used. All results were obtained after 12 months of CI activation. Results: In children, the most common etiology was idiopathic sensory-neural hearing loss. They showed positive results in the Auditory Lateralization Test. In the Speech Test, word recognition in noise improved from 2% preoperatively to 61.1% at a mean follow-up of 1 year (S0 condition) in children [test with signal in CI side 60% and signal normal hearing side (plugged) 31%]. The processor was used for >12 h in all cases. With respect to the SSQ questionnaire, parents were more satisfied within the postoperative period than within the preoperative period. For adults, the most common etiology was idiopathic sudden sensorineural hearing loss (SNHL). Positive results in the Auditory Lateralization Test were found. With respect to the Speech Test in quiet conditions: Word recognition in noise improved from 5.7% preoperatively to 71.8% at a mean follow-up of 1 year [test with signal in CI side 68% and signal normal hearing side (plugged) 41%]. The processor was used for >12 h. In the SSQ questionnaire, the post-operative results showed a beneficial effect of the CI. No adverse events were reported during the study period. No differences were found between children and adults in all tests in this study. Conclusions: Cochlear implantation in post-lingually deaf adults and children with SSD can achieve a speech perception outcome comparable with CI in conventional candidates. Improvements in spatial hearing were also observed. Careful patient selection and counseling regarding potential benefits are important to optimize outcomes.